Sprinting for the win: Distribution of power output in women`s professional cycling - Peiffer, J. J.; Abbiss, C. R.; Haakonssen, E. C.; Menaspà, P. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To examine the power-output distribution and sprint characteristics of professional female road cyclists. Methods: A total of 31 race files, representing top 5 finishes, were collected from 7 professional female cyclists. Files were analyzed for sprint characteristics, including mean and peak power output, velocity, and duration. The final 20 min before the sprint was analyzed to determine the mean maximal power output (MMP) consistent with durations of 5, 15, 30, 60, 240, and 600 s. Throughout the race, the number of efforts for each duration exceeding 80% of its corresponding final 20-min MMP (MMP80) was determined. The number of 15-s efforts exceeding 80% of the mean final sprint power output (MSP80) was determined. Results: Sprint finishes lasted 21.8 (6.7) s with mean and peak power outputs of 679 (101) and 886 (91) W, respectively. Throughout the race, additional 5-, 15-, and 30-s efforts above MMP80 were completed in the 5th compared with the 1st-4th quintiles of the race. The 60-s efforts were greater during the 5th quintile compared with the 1st, 2nd, and 4th quintiles, and during the 3rd compared with the 4th quintile. More 240-s efforts were recorded during the 5th compared with the 1st and 4th quintiles. About 82% of the 15-s efforts above MSP80 were completed in the 2nd, 3rd, and 5th quintiles of the race. Conclusions: These data demonstrate the variable nature of women`s professional cycling and the physical demands necessary for success, thus providing information that could enhance in-race decision making and the development of race-specific training programs.